Approach to adolescents with suicidal ideation - Toapanta Yugcha, Iván Guillermo; Toapanta Paredes, Ximena Elizabeth; Marín Marcano, César José; Flores Melo, Sandy Pamela (Salud, Ciencia y Tecnología - Serie de Conferencias, 2023)
Introduction: Suicidal ideation is the presentation of self-destructive thoughts in apparently normal adolescents, it is a key predictor of future suicide attempts or completed suicide; worldwide and Ecuador, it is a significant public health problem, the etiology is multifactorial, the approach is difficult due to several factors such as social stigma, personal fears and denial, difficulty expressing their feelings and thoughts, several scales have been designed. . that help for early diagnosis and prevention, the main evaluation methods are Beck, Plutchik and ISO-30, intervention programs seek to create a protective environment through group and educational activities; Intervention strategies range from environmental awareness to cognitive-behavioral therapies. These programs seek to raise awareness, provide coping skills and support based on specific needs.Objective: to carry out a systematic review that allows us to analyze and determine the approach, risk factors and evaluation scales of adolescents with suicidal ideation, using updated scientific evidence, with the purpose of facilitating health personnel in the early identification and diagnosis of the school adolescents with suicidal ideation to avoid a fatal outcome.Method: an exhaustive search was carried out in PubMed, Google Scholar, SciELO and Redalyc using Boolean operators, articles in English and Spanish published in the last five years were analyzed, allowing the selection of original studies, systematic reviews and meta-analysis, in addition to exclude studies not relevant to the age group under study or that lacked a relationship with suicidal ideation.Results: three key tools are described to evaluate suicidal ideation: the Plutchik Suicidal Risk Scale (ERSP), the ISO-30 Suicidal Orientations Inventory and the Beck Hopelessness Scale (BHS). The ERSP, adapted by Páez to Spanish, consists of 15 items and evaluates impulsivity, suicidal ideation and other related aspects. The ISO-30, validated in Spanish by Liporace and Casullo, addresses dimensions such as hopelessness, low self-esteem and loneliness, difficulty coping with emotional problems and suicidal thoughts. The BHS, developed by Beck, evaluates hopelessness and has 20 questions with true answers. or false, being a relevant indicator of possible suicidal behavior according to its total score.Conclusions: suicidal ideation, suicide attempt and completed suicide have emerged as an important public health problem worldwide in the young population. In our country, the provinces of Pichincha and Azuay are the ones that have recorded the highest cases, the early identification of Suicidal ideation is crucial to prevent premature deaths, effective prevention and addressing require a comprehensive approach combining individual and community interventions, highlighting the importance of identifying risk factors and the implementation of preventive programs.